HUBUNGAN RIWAYAT ATOPIK DAN PERSONAL HYGIENEDENGAN KEJADIAN DERMATITIS KONTAK IRITAN PADA PEGAWAI LAUNDRY DI KECAMATAN CINERE TAHUN 2019 - Salma Wangie Fauziyyah (2019)
Workers are most susceptible to skin diseases, especially irritant contact dermatitis (DKI), irritant contact dermatitis is an abnormal condition of the skin caused or exacerbated by irritants related to the work environment many factors affect the incidence of irritant contact dermatitis (DKI), one of which is a history of atopic and personal hygiene. This study aims to determine the relationship of atopic history and personal hygiene of irritant contact dermatitis (DKI) in laundry workers in the cinere district. The design of this study used a cross sectional method. The results showed that of 100 employees with a history of atopic by 51% and no history of atopic 49%, and 20% of employees had good personal hygiene and 80% of employees had bad personal hygiene. And also 54% of employees affected by Irritant Contact Dermatitis (DKI). The results of bivariate analysis with Chi-Square test found that there was a relationship between atopic history (p = 0.003), and personal hygiene (p = 0.002) with the incidence of Irritant Contact Dermatitis (DKI)